ROOT RESORPTION DURING LEVELING AND ALIGNING PHASE OF ORTHODONTIC TREATMENT – A RADIOGRAPHIC STUDY - FARIDHA S; NAVANEETHAN R (Innovare Journal Health Sciences, 2019)
Aim: This study aims to evaluate the root resorption (RR) during the leveling and aligning phase in patients undergoing fixed orthodontic treatment. Objective: This study helps in evaluating RR of anterior teeth during leveling and aligning phase of orthodontic treatment. Methods: This study involves 12 patients undergoing fixed appliance mechanotherapy. The roots of the anterior teeth root were evaluated for RR in each of these patients at 2 time intervals (a) at the start of fixed orthodontic treatment and (b) at the end of leveling and alignment with the help of either two-dimensional digital radiograph or three-dimensional cone-beam computed tomography. Results: Computerized evaluation of apical RR showed that the mean averaged RR was 0.53 mm (standard deviation [SD] 0.47) for all four incisors; the average for the central incisors was 0.48 mm (SD 0.53). Conclusions: RR can be detected even in the early leveling stages of orthodontic treatment. About 25% of patients have an average resorption of up to 2 mm of the four maxillary incisors, in the leveling and alignment phase of fixed appliance therapy. Although teeth with long, narrow, and deviated roots are at increased risk of resorption during this early stage, the explained variance of these risk factors is <25%.